PENERAPAN APLIKASI MSBE SEBAGAI MEDIA ALAT BANTU GURU BIMBINGAN KONSELING PADA SMK FADILAH - Ruli Supriati; Nirwan Salim; Ramdani Sofhan (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2015)
This research aims to help alleviate the task of teachers Counseling. Because in an educational institution such as a school in all their activities can not be separated from the role of a teacher, such as the role of teacher’s Counseling. Counseling is the task of teachers to work with students who have problems. Where students who have problems in their daily need of special attention on the problem that has been done, the limited number of teachers BK is a constraint in monitoring troubled students. Application-based monitoring troubled students on this website is used as a tool to monitor the state of the student. With this application, especially in the field of school counseling can monitor and report on the condition of students getting in trouble and facilitate parents to get information about the activity or activities of their children while in school.